Comparison of the Reliability and Validity of Math Anxiety Scale with Different Scale Formats - Duyapat, Christony G.; Lanote, Jonabel Y.; Homiggop, Sarah L.; Gamboc, Sharmaine B. (Future Science / FSH-PH Publications, 2023)
The study compared the reliability and validity of the Math Anxiety Scale (MAS) in different scale formats: 5-point scale, checklist, visual analog scale, and 4-point scale. Specifically, it sought to assess the student’s level of math anxiety, determine the reliability coefficients of each scale format, test the concurrent validity against the standardized scale, and compare the extracted factors with the original MAS. The respondents were 67 students, a total enumeration from two sections of a laboratory school in La Trinidad, Benguet. The standardized MAS (5-point scale) was adopted and transformed into a checklist, visual analog scale, and 4-point scale. The tests were administered at three-day intervals. The findings indicated that students experienced a moderate level of math anxiety, with cognitive dimension substantially contributing to their anxiety. The visual analog scale demonstrated the highest reliability coefficient, followed by the 4-point scale, checklist, and 5-point scale, respectively. Concurrent validity analysis revealed that the visual analog scale exhibited the highest concurrent validity, followed by the 4-point scale and checklist, respectively. Based on the results, the majority of the students are experiencing a moderate level of math anxiety. Among the four scale formats, the visual analog scale provides the most reliable and valid responses to be used in measuring math anxiety among junior high school students with ages ranging from 11 to 13 years old.